Toxicity of Selected Insecticides (Spinosad, Indoxacarb and Abamectin) Against the Diamondback Moth (Plutella xylostella L.) On Cabbage - Ismail, Fauziah; M. T. , Mohd Norazam; Rasdi Z. , Mohd (Asian Journal of Agriculture and Rural Development, 2012)
Plutella xylostella L. is a most serious of insect pest for cruciferous or Brassica crops throughout the world. The common name of this insect pest is the Diamondback Moth (DBM). Plutella xylostella L. is an oligophagous insect which is feed on the group of botanically plants within the single plant family. This insect has become major serious problem to the crops because it easily and rapidly develops their resistance to insecticides. Insecticides were used to kill Plutella xylostella L. that contribute to minimize the level of infestation. Toxicity levels were measured by lethal concentration (LC50) to estimate the effectiveness of selected insecticides. A total of three selected insecticides namely spinosad, indoxacab and abamectin had been tested against Plutella xylostella L. The data of LC50 was analyzed using PROBIT program. The result from this study had been used to estimate the effective dose or quantity of each insecticide need for controlling Plutella xylostella L. Besides that, the most effectiveness between the tested insecticides were selected for managing Plutella xylostella L. Results from this study shows that indoxacarb were most effective and toxic to control Plutella xylostella L. compared with spinosad and abamectin because it gave lower LC50 value (1010.080). In term of concentration, indoxacarb (1125 µl/5000 ml) and spinosad (2750 µl/5000 ml) was the effective concentrations for controlling Plutella xylostella L. by mortality rate more than 50%, 60% and 80% respectively.